Stilistika Al-Qur’an: Memahami Bentuk-Bentuk Komunikasi Dalam Surah Asy Syu’ara’ - Tri Tami Gunarti,; Mubarok Ahmadi (Al Furqan: Jurnal Ilmu Al Quran dan Tafsir, 2021)
This paper reveals the linguistic phenomenon of the Qur'an with the central theme of forms of communication in Surah as-Syu'ara'. The problems studied include stylistics from aspects of phonology, morphology, syntax, and semantics in verses relating to forms of communication, which are limited to surah ash-Syu'ara'. In Surah ash-syu'ara' there are several verses that contain several communisms, so the author is interested in analyzing using stylistics to reveal the linguistic phenomena of these verses. This paper is expected to be a reference for the development of other linguistic studies that take the same object, namely the Qur'an. This writing proves and shows that there is a spectacular value charge in the language of the Qur'an which is known as the content of i'jaz al-Qur'an. The theory used is the stylistic theory which the author limits to only three things: preference for lafadz, preference for sentences or the preferred meaning in a sentence, and deviations or deviations from the general rules of grammar. the object of the study is the construction of various forms of communication in the surah ash-Syu'ara'.